2014
DOI: 10.3727/096368914x684989
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stem Cell-Conditioned Medium Protects Neurons and Promotes Propriospinal Neurons Relay Neural Circuit Reconnection after Spinal Cord Injury

Abstract: Human fetal neural stem cells (hNSCs) are used to treat a variety of neurological disorders involving spinal cord injury (SCI). Although their mechanism of action has been attributed to cell substitution, we examined the possibility that NSCs may have neuroprotective activities. The present article studied the action of hNSCs on protecting neurons and promoting corticospinal tract (CST) axon regeneration after SCI. hNSCs were isolated from the cortical tissue of spontaneously aborted human fetuses. The cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 49 publications
1
42
0
Order By: Relevance
“…suggesting that CM-hNSC has a beneficial effect on the survival of differentiated SH-SY5Y cells. A previous in vivo study by other investigators showed that CM-hNSCs can reduce the number of caspase 3-positive apoptotic profiles of spinal cord injuries [11]. Consistently, our results further confirmed that the decreased number of differentiated SH-SY5Y cells is due to apoptosis resulting from RA treatment, whereas CM-hNSCs can protect these RA-differentiated SH-SY5Y cells --from apoptosis, as demonstrated by the PI/annexin V staining results ( Fig.…”
Section: Ra-differentiated Sh-sy5y Cellssupporting
confidence: 91%
“…suggesting that CM-hNSC has a beneficial effect on the survival of differentiated SH-SY5Y cells. A previous in vivo study by other investigators showed that CM-hNSCs can reduce the number of caspase 3-positive apoptotic profiles of spinal cord injuries [11]. Consistently, our results further confirmed that the decreased number of differentiated SH-SY5Y cells is due to apoptosis resulting from RA treatment, whereas CM-hNSCs can protect these RA-differentiated SH-SY5Y cells --from apoptosis, as demonstrated by the PI/annexin V staining results ( Fig.…”
Section: Ra-differentiated Sh-sy5y Cellssupporting
confidence: 91%
“…Cantinieaux et al reported that BMSC-CM administered after spinal cord contusion improves motor recovery in rats (18). Moreover, Liang et al showed that neural stem cell conditioned medium promoted locomotor recovery in adult rats after spinal cord injury (29). In addition, Torrente et al reported that paracrine factors of human mesenchymal stem cells are a useful neuroprotective approach for brain recovery following injury (30).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the initial perception that NSC transplantation only served to replace lost cells, recent experimental studies have shown that transplanted NSCs also exert additional bystander effects such as the neuroprotection that promote tissue repair (Aharonowiz et al, 2008). To verify this characteristic of NSCs, Liang et al (2014) removed the neural stem cell from a normal culture medium to acquire neural stem cell-conditioned medium to exclude the effect of cell substitution. Results showed that continuous administration of conditioned medium in rats with spinal cord injury increases bridging between the corticospinal tract and intermediate neurons reduces neuron apoptosis, and promotes the recovery of motor function.…”
Section: Protect Neuronsmentioning
confidence: 99%